Генна терапія: особливості та досвід застосування при експериментальному атеросклерозі - Піскун, Р.П.; Білошицька, А.В.; Гринчак, Н.М.; Шевчук, Т.І.; Горбатюк, С.М.; Піскун, І.І.; Ромашкіна, О.А.; Савицька, А.А. (Фактори експериментальної еволюції організмів, 2014)
Aim. Defining the structural peculiarities of parenhyma as well as blood vessels of heart, liver, kidneys, lungs, thyroid gland in their norm, in condition of the designed pathology and in the case of its gene correction. Comparing the obtained results in order to evaluate the influence of the preventing effect as well as the medicinal one in the condition of Apo-E gene injection taking into account the morphological and functional changes of studied structures of organs. Methods. Modeling, macromorphometrical, histological, histochemical, micrometrical, electronic microscopic, biochemical and statistic methods. Results. Atherosclerosis was determined to reproduce the lipid spectrum changes of blood serum as well as the localized necrosis of the parenhyma’s cell elements and the sroma’s fibrosis as a result of the reduced arterial vessels capacity and due to the disfunction of the microvasculature. Conclusions. Preventive usage of Apo-E gene as well as its medicinal application in the condition of the experimental atherosclerosis results the reduced pathological changes in the arteries and in the vessels of the microvasculature, and it improves the blood supply in the organs which have been studied.

Key words: experimental atherosclerosis, gene therapy, morphology.